Antibacterial property improvement of nano-MgO prepared by lithium doping under nitrogen calcination. Issue 8 (15th April 2021) - Li, Xiaoyi; Zhao, Jiao; Bai, Xiaodan; Yang, Yan; Ma, Qiao; Tang, Xiaojia; Wang, Yin; Zhu, Yimin
Abstract: MgO nanomaterial (nano-MgO) is a promising candidate in the antibacterial field owing to its large reserves, low cost, high stability, and safety to both the environment and human beings. However, the actual application of nano-MgO is restricted by its relatively low antibacterial activity. In the present work, we report the fabrication of modified nano-MgO via lithium (Li) ion doping and an oxygen-deficient calcination process. The antibacterial ratio of Li/MgON at 100 μg/mL was about 99.6% against 10 8 CFU/mL Escherichia coli ( E. coli, ATCC 25922), suggesting that the antibacterial activity was successfully enhanced compared with that of pure MgO and Li/MgO calcined in air. This superior activity mainly originated from the increased number of oxygen vacancies based on the synergetic effects of Li doping and N2 calcination, resulting in more O2 − generation. The disinfection of drinking water tests showed that Li/MgON quickly killed E. coli in 1 h and retained high activity over 30 days. These results indicated that the formation of modified nano-MgO by Li doping and N2 calcination is a novel and effective approach to obtain a promising MgO-based antibacterial agent with highly effective antibacterial property and durability.